The analysis of SUDEP forensic autopsies leading to preventable events - Argo, Antonina; Puntarello, Maria; Malta, Ginevra; Buscemi, Roberto; Scalzo, Giovanni; Triolo, Valentina; Albano, Giuseppe Davide; Zerbo, Stefania (Frontiers in Neurology, 2023)
The diagnosis of unexpected death by excluding non-natural causes, particularly in subjects with epilepsy, is an interest topic and it is difficult to identify in the forensic field. We sometime are faced with cases of sudden death, generally in young adults with a long history of epilepsy that require, for judicial purposes, an explanation in terms of cause and means that determine the death. SUDEP is an entity diagnosed by exclusion of other causes that may have led to death, and then for forensic purposes it requires particular attention and knowledge, as well as difficulty in identifying it. Our contribution aims to share with the scientific community pathological findings, medical history, and circumstantial evidence of four cases of sudden death in epileptic subjects. These are four cases at first judicial autopsies from the Palermo's Institute of Forensic Medicine in which the purpose was to exclude the criminal intervention in determining death as non-natural. The victims' medical history study, the toxicological investigations, and the autopsy findings analyzed both from a macroscopic and microscopic aspects have made it possible to highlight some findings that can be traced back to SUDEP, despite the small sample of subjects studied. This could help forensic pathologists in recognizing SUDEP, highlighting its characteristics, and allowing for a physio-pathological classification also related to the use of drugs for the epilepsy treatment. All of this, also considering the literature review with criticism, could allow us to select the characteristics of epileptic patients at risk of sudden death.